Foraging strategy influences the quantity of ingested micro- and nanoplastics in shorebirds. (15th February 2023) - Mylius, Karli A.; Lavers, Jennifer L.; Woehler, Eric J.; Rodemann, Thomas; Keys, Bianca C.; Rivers-Auty, Jack
Abstract: Coastlines, including estuaries, mudflats, and beaches, are particularly susceptible to plastic pollution, which can accumulate from both marine and terrestrial sources. While numerous studies have confirmed the presence of microplastics (1–5 mm) along coastlines, few have focused on very small particles (<1 μm) or quantified exposure within the organisms that inhabit these areas, such as shorebirds. Here, we quantified small plastics (200 nm–70 μm) in two resident shorebird species in Tasmania, and compared this to quantities found in the surrounding sediments in order to investigate the potential exposure and transfer of particles within these ecosystems. Analysis was performed using a combination of flow cytometry for quantification of micro- and nanoplastics (200 nm–70 μm), and μm-FT-IR for validation and polymer identification of particles >5.5 × 5.5 μm. Micro- and nano-plastics were detected in 100% of guano samples from surface-feeding Eastern Hooded Plovers ( Thinornis cucullatus ) and 90% of Australian Pied Oystercatcher ( Haematopus longirostris) guano, a species that forages for coastal invertebrates at 60–90 mm depth, and 100% of beach sediments. Hooded Plover guano contained 32 × more plastics, on average, than Pied Oystercatcher guano. Interestingly, the abundance of plastic particles within sediments collected from shorebird foraging sites did not appear to have a significant effect on the number of plastics the birds had ingested, suggesting the difference between species is likely a result of other variables, such as prey selection. The results of this study highlight the importance of including techniques that provide quantitative data on the abundance and size of the smallest possible particle sizes, and demonstrate the significant proportion of small plastics that are 'missed' using standard analysis tools. Graphical abstract: Image 1 Highlights: Micro- and nano-plastic found in all sediment samples from 10 Tasmanian sites. Micro- and nano-plastic uptake varied with shorebird beak length. Plover guano contained 3 × more plastics, on average, than oystercatcher guano. Plovers foraging within the beach sediment surface were exposed to more plastics.